2005
DOI: 10.1016/j.ydbio.2005.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila myosin V is required for larval development and spermatid individualization

Abstract: Class V myosins are multifunctional molecular motors implicated in vesicular traffic, RNA transport, and mechanochemical coupling of the actin and microtubule-based cytoskeletons. To assess the function of the single myosin V gene in Drosophila (MyoV), we have characterized both deletion and truncation alleles. Mutant animals exhibit no detectable defects during embryogenesis but are delayed in larval development; most die prior to 3rd instar. MyoV protein is widely distributed; however, there are no obvious c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
39
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 73 publications
7
39
1
Order By: Relevance
“…In regard to sperm individualization, the testes of 19 lncRNA KO mutants, including CR42858 −/− and CR43282 −/− , exhibited defects in coordinated actin cone movement, resulting in poorly aligned or lagging ICs. Similar phenotypes have been reported for the mutants in the genes encoding the testis-specific proteasome subunit Prosα6T, myosin VI, myosin V, and dynein (Hicks et al 1999;Li et al 2004;Mermall et al 2005;Zhong and Belote 2007). It remains to be determined whether these lncRNAs are directly functional in late spermatogenesis or instead play a role in the early spermatogenesis that is only manifest in the late stage.…”
Section: Discussionsupporting
confidence: 58%
“…In regard to sperm individualization, the testes of 19 lncRNA KO mutants, including CR42858 −/− and CR43282 −/− , exhibited defects in coordinated actin cone movement, resulting in poorly aligned or lagging ICs. Similar phenotypes have been reported for the mutants in the genes encoding the testis-specific proteasome subunit Prosα6T, myosin VI, myosin V, and dynein (Hicks et al 1999;Li et al 2004;Mermall et al 2005;Zhong and Belote 2007). It remains to be determined whether these lncRNAs are directly functional in late spermatogenesis or instead play a role in the early spermatogenesis that is only manifest in the late stage.…”
Section: Discussionsupporting
confidence: 58%
“…Although the mechanism of the actin cone movement has not been fully elucidated, it has been proposed that actin polymerization and depolymerization are the driving force (Noguchi and Miller, 2003). Myosin VI seems to be an actin cone structure stabilizer (Noguchi et al, 2006), and myosin V is required for actin cone formation (Mermall et al, 2005). Here, we demonstrate that the ubiquitin-proteasome pathway is also important in IC movement.…”
Section: Possible Roles Of Testis-specific Proteasomes In Sperm Indivmentioning
confidence: 56%
“…Our observations that in the Pros␣6T 1 mutant, active Dronc disappears from the IC and active Ice is significantly reduced is consistent with this model. The fact that active Ice is not completely eliminated suggests that there might be an additional Dronc-independent pathway for Ice activation, as has been suggested by Huh et al (Huh et al, 2004 (Hicks et al, 1999;Li et al, 2004;Ghosh-Roy et al, 2005;Mermall et al, 2005). The spermatid nuclear bundles in these mutants are also disrupted.…”
Section: Possible Roles Of Testis-specific Proteasomes In Sperm Indivmentioning
confidence: 82%
“…Although Myosins V and VI are important for this process, motor activity does not seem to power migration of the IC. 23,[27][28][29] The observation that actin polymerization is essential for IC progression suggests that the IC moves by incorporating new actin filaments at the cones, 21,27 and experimental evidence indicates that the rear bundles specifically are involved. 25 Classical genetic studies have identified at least 70 genes that mutate to give individualization phenotypes ( Table 1).…”
mentioning
confidence: 99%